Seawater corrosion resistant heat transfer agent (HTA) to improve water evaporation in solar still - Chew, Few Ne; Abd Rahim, Syarifah; Cheng, Chin Kui (2016)
Solar still is an economical technique for water desalination, however its main drawback is low productivity. In this project, a heat transfer agent (HTA) was installed in a solar still aimed to distribute the heat throughout the seawater and increase the water evaporation rate. Copper was selected as the HTA due to its high electrical and thermal conductivities. However, seawater may cause copper corrosion; hence coating is required to avoid the metal deterioration. The present study reported the effects of coating material and thickness, and the incubation temperature on the copper corrosion rate and heat transfer rate. Copper rods coated with different coating material have low weight loss and corrosion rate if compared with bare copper rod. Besides, weight loss and corrosion rate with incubation temperature of 25°C were relatively high if compared with incubation temperature of 60°C. Moreover, an increase in the coating layer linearly increased the mass of the coated copper rods. Under the steady-state condition, the thermal conductivities increased when the coating layer was increased further. Hence, adding the coating layer reduced the radial heat transfer rate and higher axial heat transfer rates were obtained. A solar still was designed and fabricated. HTA consists of a sheet of copper plate and 12 pieces of copper rods. Two set of experiment set-up were conducted to investigate the effect of HTA on the solar still performance. In general, water and glass temperatures and evaporative heat transfer of solar still with HTA were higher than the solar still without HTA. Experiment data have revealed the function of the HTA that may quickly transferred the radiation energy from the copper plate and rods to the water. The introduction of the HTA has successfully increased 30% of water evaporation rate and 18% of thermal efficiency.